Tooth Lightness Changes with Listerine Healthy White after Application of Tooth-Coloring-Inducing Foods - Moon-Jin Jeong; Jung-Hui Son; Soon-Jeong Jeong; Ye-Jin Kim; Hee-Jung Lim; Im-Hee Jung; Do-Seon Lim (치위생과학회지, 2023)
Background: The purpose of this study is to investigate the tooth whitening effect of Listerine Healthy White and provide effective management of extrinsic discoloration by comparing the whitening effects of existing whitening products.Methods: The included study four groups: those using whitening gel, whitening toothpaste, and Listerine Healthy White and a control using artificial saliva. Each group received 40 bovine tooth specimens, which were stained with commonly consumed tooth-coloring-inducing foods; black tea, black coffee, and instant noodles for 72 hours. The specimens were treated with tooth whitening materials for 5 weeks, after which the lightness (L*) was measured weekly using a spectrophotometer. Results: There was a significant difference in lightness among the groups between the 1st and 5th week of treatment for all tooth-coloring-inducing foods (p＜0.05). When comparing the changes in lightness values from before whitening to the 5th week of whitening for all tooth-coloring-inducing foods, the order of change was as follows: whitening gel, whitening toothpaste, Listerine Healthy White, and artificial saliva. Listerine Healthy White showed a significant whitening effect for all tooth- coloring-inducing foods (p＜0.05). Particularly, changes in lightness values for specimens stained by black tea after 5 weeks of whitening were in the following order: whitening gel (21.72), whitening toothpaste (14.89), Listerine Healthy White (12.91), and artificial saliva (3.85). For specimens stained by black coffee, the changes in lightness values were in the following order: whitening gel (12.99), whitening toothpaste (9.66), Listerine Healthy White (7.91), and artificial saliva (3.12). Lastly, changes in lightness values for specimens stained by instant noodles were as follows: whitening gel (10.84), whitening toothpaste (9.85), Listerine Healthy White (7.71), and artificial saliva (2.61). Conclusion: Listerine Healthy White exhibits continuous whitening effects over time, and for consumers seeking convenient ways to achieve tooth whitening effects at home, consistent use of Listerine Healthy White is recommended.